Advanced fatigue verification method for record breaking bridges. Issue 2 (1st September 2021) - Bjærre, Simon; S⊘rensen, Jesper W.; Polk, Henrik
Abstract: Designing and reviewing suspension bridges with world record breaking main spans in countries like Turkey, China and Norway requires a new and advanced method for fatigue verification. COWI's in‐house software IBDAS (Integrated Bridge Design and Analysis System) is used to perform the full fatigue verification including load modelling, finite element modelling, stress history analysis and damage evaluation based on the damage accumulation method. Discussions of boundary conditions are avoided by utilizing a global IBDAS beam model for the overall static system. A few segments of the girder in the global model are replaced by a semi‐local shell model in which a fine local shell model with all local geometry is placed at the location of interest. Fatigue data points used for verification are defined in the local model, typically based on hot‐spot extrapolation methods. In IBDAS, the extrapolation can be defined whereby the fatigue data point stress histories can be used directly for fatigue evaluation with the reservoir cycle counting method. Hereby, time‐consuming bookkeeping of FE node output is avoided. This paper presents technical aspects of the fatigue verification method used for the latest suspension bridge designs including the advantages of utilizing a fully integrated system.